2016
DOI: 10.1021/acsami.5b08990
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Electrical Transport Across Metal–Thermoelectric Interfaces Using a Nanomolecular Monolayer

Abstract: We report a 13-fold increase in electrical contact conductivity Σc upon introducing a 1,8-octanedithiol (ODT) monolayer at Cu-Bi2Te3 interfaces. In contrast introducing ODT at Ni-Bi2Te3 interfaces results in a 20% decrease in Σc. Rutherford backscattering spectrometry, X-ray diffraction and electron spectroscopy analyses indicate that metal-sulfur and sulfur-Bi2Te3 bonds at metal-Bi2Te3 interfaces inhibit chemical mixing, curtail metal-telluride formation, and suppress oxidation. Suppressing p-type Cu2Te favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
5
17
1
Order By: Relevance
“…We did not see a clear visible contrast at the Al/ZrTe 5 interface in the SEM images (Figure S1 in the Supporting Information), which indicates there is no significant Al atom diffusion into ZrTe 5 . This is in contrast to previous work showing that metal atoms, such as Pd, can diffuse into ZrTe 5 crystals when they are in contact, and other metal atoms (e.g., Cu, Ni, Co, or Fe) diffuse into topological insulators (e.g., Bi 2 Se 3 ) and thermoelectric materials (e.g., Bi 2 Te 3 ) …”
Section: Resultscontrasting
confidence: 97%
“…We did not see a clear visible contrast at the Al/ZrTe 5 interface in the SEM images (Figure S1 in the Supporting Information), which indicates there is no significant Al atom diffusion into ZrTe 5 . This is in contrast to previous work showing that metal atoms, such as Pd, can diffuse into ZrTe 5 crystals when they are in contact, and other metal atoms (e.g., Cu, Ni, Co, or Fe) diffuse into topological insulators (e.g., Bi 2 Se 3 ) and thermoelectric materials (e.g., Bi 2 Te 3 ) …”
Section: Resultscontrasting
confidence: 97%
“…This may be due to two combined effects. One is the reduction of some compounds at the interface, which decreases the R c . Another is the increase of the R sh from TLM, which may result from the lower doping effect of Cu on Bi 2 Te 3 through diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…But, loading-frequency-dependence of interfacial fatigue, and related phenomena, remain largely unexplored. Our prior work has shown that introducing an interfacial molecular nanolayer (MNL) in model polymer-metal-ceramic structures can yield multifold increases in fracture energy under static loading 16 19 , enhance thermal 20 and electronic 21 25 transport, inhibit diffusion 26 28 , and alter phase formation 29 . However, the effects of cyclic loading on the fracture behavior of such molecularly modified model systems are not known.…”
Section: Introductionmentioning
confidence: 99%